KONTRIBUSI SISTEM CIVIL LAW (EROPA KONTINENTAL) TERHADAP PERKEMBANGAN SISTEM HUKUM DI INDONESIA - Firdaus Muhamad Iqbal (Law Department Jenderal Achmad Yani University, 2022)
The legal system is a set of regulations, including commands, restrictions, and permissibility. The Civil Law System and the Anglo-Saxon System are the two legal systems now in use in the world. As a legacy of the Dutch colonial authority, Indonesia follows the Civil Law system, or Continental Europe. A normative legal research methodology using secondary data types was used. The Civil Law system, which emerged in countries in Mainland Europe and was codified from Ancient Roman Law, is the subject of this study's findings and discussion. The 13th century saw the beginning of the movement of this system, which has a lengthy history and is inextricably linked to economic, political, and intellectual forces in Western Europe. This system of laws acknowledges the division between public and private law. The Civil Law system is characterized by the existence of a codification or legal record that preserves the law and serves as a foundation or mechanism for judges to act and uphold the legal system documented in the law. The three dimensions of the national legal order, which is based on the Civil Law legal order, are the maintenance dimension, the renewal dimension, and the creative dimension. Along with these features, the Civil Law system also strengthens Indonesia's legal framework by, among other things, creating new laws, discovering new laws, and using judges as law's mouthpieces to enforce laws that affect people's daily lives.